Enclitic Pronouns In The Anbarāni Dialect Of Talyshi - Hakob Avchyan (Banber Arevelagitut'yan Instituti)
Enclitic pronouns are used in most of New West Iranian languages. They are mainly used for marking the possessor, as well as objects, besides, those Iranian languages and dialects, which show ergative patterns, make use of enclitic pronouns for marking the agent in ergative constructions. This paper deals with the enclitic pronouns and their functions in Anbarāni, one of the Northern Talyshi dialects, spoken in the Islamic Republic of Iran. Where it is possible the features of Anbarāni enclitics will be compared with some other West Iranian languages.